The Mirror of Simple Souls - Porete, Marguerite, approximately 1250-1310 (Book collections on Project MUSE., 1999)
As a result, this edition offers a reading of The Mirror which solves a number of difficulties found in the French, and the introduction contributed by the translators narrates the archival history of the book for which Margaret Porette was burned alive in Paris in 1310"--Jacket